Detection of antibody responses by using haemagglutination inhibiton test and the protection titer of avian influenza virus H5N1 subtype - Risa Indriani; N.L.P.I Dharmayanti; A Wiyono; Darminto .; L Parede (Indonesian Center for Animal Research and Development (ICARD), 2004)
Study on the detection of antibody responses using haemagglutination inhibition (HI) test and the protection titer to Avian influenza (AI) virus H5N1 subtype local isolate has been conducted at the Research Institute for Veterinary Science (RIVS). A total number of 50 village chicken (10 chicken served as un-injected controls) and 30 quail were injected intramuscularly with inactivated virus of AI H5N1 subtype local isolate. Serum samples were collected 3 weeks after injection and were tested using haemagglutination inhibition tests. The correlation between antibody titer and its protection to AI virus H5N1 local isolate were measured by challenging the birds with AI virus H5N1 local isolate The HI test was then used to determine field serum samples. A total number of 48 village chicken from three (3) Districts (Bekasi, Tangerang and Bogor) and 96 quails from two (2) farms in District of Sukabumi which were all vaccinated with commercial AI adjuvant vaccine were sampled. The study revealed that village chicken and quails showed antibody responses after 3 weeks vaccination and that titer of ≥ 3 log 2 was able to protect chicken and quails when they were challenged with local isolate virus. Based on this result, village chicken field samples from Districts of Tangerang, Bekasi and Bogor showed antibody titer which will protect 50, 100 and 85% of the flocks respectively. While quail field samples from Farm I and Farm II in District of Sukabumi showed antibody titer which will protect 60-100% and 0-80% of the flocks respectively. It is concluded that the study has successfully measured antibody titer to AI virus H5N1 subtype which protect village chicken and quails from local isolate virus challenge so that the results will be used to analyze field serum samples after vaccination program to eradicate AI from Indonesia. Key words: Antibody responses, haemagglutination inhibition test, protection titer, AI virus H5N1subtype